PENGARUH NILAI TUKAR, INFLASI, VOLUME PERDAGANGAN, DAN DIVIDEND PAYOUT RATIO TERHADAP SHARE PRICE VOLATILITY PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS KOMPAS100 TAHUN 2014 – 2018 - mastura, Mastura (Fakultas Ekonomi dan Bisnis Islam, 2021)
This research aims to analyze partial and simultaneous influence between exchange rate, inflation, trading volume, and dividend payout ratio to share price volatility in Kompas100 index. This research uses 23 companies listed in Kompas100 index as a research sample during the period of 2014 to 2018, where sampling uses purposive sampling technique. In order to analyze, and test each research hypotheses, the technique used is panel data regression using the random effect model. The results of data analysis show that partially, the excgange rate, inflation, and trading volume have a positive and significant effect to share price volatility while the dividend payout ratio has a negative and significant effect to share price volatility. the results of data analysis show simultaneously, the exchange rate, inflation, trading volume, and dividend payout ratio have significant influence to share price volatility. The amount of testing the coefficient of determinastion (adjusted R square) is 0.416174, indicating that dependen variable which is share price volatility can be explained by independent variables those are exchange rate, inflation, trading volume, and dividend payout ratio was 41.6%, while 58.4% can be explained by the other variables outside the models